VACTERL(S) Association – A Case Report - Senthil Kishore (JK Science, 2025)
VACTERL (vertebral, anal, cardiac, tracheoesophagus, renal, and limbs) is an acronym of a spectrum of congenital abnormalities. It is an uncommon blastogenesis anomaly affecting a wide range of organs. The pinpoint aetiology is not well understood. Various genetic aberrations and environmental causes are stipulated. We publish a case of a 33 weeks and 6 days old foetus with the fore-mentioned anomaly. This case iterates the critical relevance and significance of a specialized pathologist in performing perinatal autopsy to confirm the presentation.